Beneath the Lion's Head - Chatterjee, Anirban ([Maribyrnong, Vic.] : [Anirban Chatterjee], 2018)
Annotation. Beneath The Lion's Head is a 42 image photobook that mixes the old eastern supernatural tales, the Hong Kong stereotypes of 90's movies and the photographer's childhood memories of Hong Kong based on detective stories, graphic novels, and pop culture ephemerals.
"A Street Etoki Production" -- last page.
Keywords: Photography, Artistic; Photobooks -- China -- Hong Kong; Hong Kong (China) -- In art